PENGARUH PERILAKU MENCARI VARIASI MENU TERHADAP MINAT BERKUNJUNG KEMBALI YANG DIMEDIASI OLEH KEPUASAN (Studi Kasus Pada Konsumen McDonald’s di Kota Mataram) - Dani, Azan (Journal of Sharia Economy and Islamic Tourism, 2024)
This study aims to determine the effect of the behavior of seeking menu variations on return interest by mediating McDonald's consumers in the city of Mataram). The population in this study were consumers who had shopped at McDonald's in Mataram City, while the sample of this study was 120 McDonald's consumers using purposive sampling technique. This type of research is associative research. Data processing in this study using SPSS 26.0 for Windows, where validity test, reliability test, classical assumption test, path analysis test, significance test (t test), coefficient of determination test (R²) and Sobel test were carried out. The results of the analysis, all variables have a partial effect, where Menu Changes have an effect on Interest in Re-developing, Influence on Interest in Searching Again, Behavior Looking for Variations has an effect on goals. Results Based on this, it is suggested that McDonald's can increase the variety of menus and increase satisfaction so as to increase customer interest in purchasing products at McDonald's restaurants